Wellbeing subjective in the Coid-19 era - María Luisa Quintero- Soto; Sofía López de Nava- Tapia; Gerardo Arturo Limón- Domínguez; Sonia Sujell Velez- Baez; Cruz García- Lirios (HUMAN: South Asian Journal of Social Studies, 2021)
Abstract. Subjective well-being has been established as a construct with subjective, normative or perceived dimensions. It has often been related to quality of life and local development, but as a concomitant variable rather than as an effect variable. The objective of this work was to observe meta-analytical categories in order to specify a model for the study of subjective well-being according to the findings of the state of the art. A documentary and retrospective investigation was carried out with a selection of sources indexed to international repositories, considering the year of publication and the prestige of the quality of the product, although the design limited the review to the analysis sample, suggesting the extension of the work to others repositories and years. Keywords: Device, Positivity, Biopolitics, Intervention, Social Work.